PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK TERPADU KURIKULUM 2013 BERBASIS MULTIMEDIA UNTUK KELAS I SEKOLAH DASAR - Sagi Winoto; Vina Anggia Nastitie Ariawan (COLLASE (Creative of Learning Students Elementary Education), 2021)
Abstract The purpose of this research is to address the problems relating to the lack of interesting and effective x thematic learning media in class so as to improve the effectiveness of learning. The development procedure of two main objectives, namely developing the product and validating the resulting product. The population of this study was SDN 1 and SDN 2 Sesela and the research samples used were SDN Rejodadi 01 and SDN Rejodadi 04. The research instruments used were interview, test, observation, and questionnaires to validate and evaluate the quality of the developed products. Data analysis teschniques used qualitative descriptive. The results of the research were as follows: (1) The results of expert validation and teacher assessment of media products that have been developed eligible to be used, (2) Limited trial results are known that the product development is worth use and (3) field trial results are known that the product of development that has been worthy of use affects the ability to understand the students ' thematic concept.Kata Kunci: learning media, thematic, Multimedia, primary schoolAbstrak Tujuan penelitian ini adalah untuk mengatasi masalah yang berkaitan dengan minimnya media pembelajaran tematik yang menarik dan efektif dikelas sehingga dapat meningkatkan efektifitas pembelajaran. Prosedur pengembangan terdiri dari dua tujuan utama yaitu mengembangkan produk dan memvalidasi produk yang dihasilkan. Populasi dalam penelitian ini adalah SDN Rejodadi 01 dan SDN Rejodadi 04. Instrumen penelitian yang digunakan berup wawancara, tes, observasi dan angket/kuesioner untuk memvalidasi dan mengevaluasi kualitas produk yang dikembangkan. Teknik analisis data yang digunakan dengan analisis deskriptif kualitatif. Adapun hasil penelitian ini sebagai berikut: (1) hasil validasi ahli dan penilaian guru terhadap produk media  yang telah dikembangkan telah layak untuk digunakan, hasil uji coba terbatas diketahui bahwa produk hasil pengembangan layak digunakan dan (3) hasil uji coba lapangan diketahui bahwa produk hasil pengembangan yang sudah layak digunakan berpengaruh terhadap kemampuan memahami konsep tematik siswa.Kata Kunci: Media Pembelajaran, Tematik, Multimedia, SD